EVALUASI TINGKAT KERUSAKAN JALAN DENGAN METHODE PAVEMENT CONDITION INDEX (PCI) UNTUK MENUNJANG PENGAMBILAN KEPUTUSAN (Studi Kasus: Jalan Lingkar SeLatan, Yogyakarta) - Suswandi, Agus; Sartono, Wardhani; Christady H, Hary (Civil Engineering Forum Teknik Sipil, 2008)
Being functioned as the main transportation line for passengers and cargo, any distress on the pavement of South Ring Road in Yogyakarta requires rehabilitation to prevent severe condition. But before the rehabilitation is carried out, it is required to evaluate the road pavement condition. The objective of this study is to appraise or to value the road pavement condition. This research implementation was visually completed by using Pavement Condition Index Method. It was started by dividing the road into several research units in 100 x 3.5 m by size for each unit sample. Then, each of the research unit was observed and measured to identify the distress type and severity level in order to obtain PCI rating value of the pavement. Result of the study showed that the distress types included the alligator cracking, block cracking, depression, longitudinal and transverse cracking, patching, polished aggregate, shoving, slippage cracking and weathering/graveling. The prevailing ones were block cracking and alligator cracking. The damages occurred only on some parts of the segment. Therefore, it was better to adjust the treatment for such damage for the distress type. Treatment priorities should be given to sample unit 23 B (lane 1) due to its smallest PCI value, which was 22, with VERY POOR condition pavement rating.